KNOWLEDGE ENHANCEMENT REGARDING HYPERCHOLESTEROLEMIA THROUGH EDUCATION IN THE CIKUPA COMMUNITY HEALTH CENTER WORKING AREA - Shalisha Marvela Vantya; Zita Atzmardina (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Hypercholesterolemia is a risk factor for cardiovascular, cerebrovascular, and peripheral blood vessel diseases. Hypercholesterolemia cases at the Cikupa Community Health Center were reported to have increased from January-June 2022 from 147 cases to 283 cases in the January-June 2023 period. The invention aims to increase public knowledge about hypercholesterolemia. Data was collected using a mini survey and identification of the source of the problem using the Blum Paradigm. Problem priority is determined using the Delphi non-scoring method. Identify the root cause of the problem with a fishbone diagram. The activity begins by distributing pre-test sheets for respondents to fill out, then after the counseling there is a question and answer session before filling in the post-test. The successful results of counseling can be seen from the pre-test and post-test scores. The research results showed that there was success in counseling seen from the pre-test and post-test scores. The data were analyzed using the paired T test and the results showed that there was a significant mean difference (P<0.002) with a mean difference value of 12.85. Based on these results, it can be concluded that this counseling was successful.